The Problem of the Dual Pauline Eschatology in Light of the Eschatology of the Wisdom of Solomon - Brauch, Theophil Manfred (My University, 1972)
The present study is primarily an attempt to break new ground in a much debated area of Biblical Studies. The Pauline eschatology, with its complexity and diversity in eschatological conceptions and formulations, has called forth a number of scholarly solutions. The apparently unconnected juxtaposition of individualistic and corporate, end-historical eschatological conceptions in the thought of Paul has been accounted for variously as: 1) the result of development from the early to the late Paul under the influence of Hellenism; 2) the result of personal crises which turned his attention away from the end of human history to the end of his personal history; 3) the result of a mind that is unreflective and therefore does not see the contradictoriness. A further attempt at a solution is the non-recognition of the contradictoriness; and a subordination of the undeniable individualistic elements to the corporate eschatological scheme.
None of these solutions were found to be satisfactory to this writer. A careful analysis of the apocryphal work, the Wisdom of Solomon, revealed the same kind of duality of individual and corporate eschatological perspectives as in Paul. Our study further showed that this duality arises out of a conception of the presence and work of the divine figure of Wisdom in history and in the lives of men, and that this conception provides a strikingly informative background for the Pauline conception of the Christ who is Lord of history and at the same time the personal, intimate, indwelling divine presence. A detailed analysis and comparison of these configurations of like elements in the two writers suggests that Paul was influenced by the Wisdom of Solomon, particularly by that work's conception of the fate of the individual and by its depiction of union with Wisdom as the guarantee of life, both in the present and in the future.
It has always been recognized that Paul, like any other outstanding figure of history, was dependent on streams of thought that crossed the contemporary atmosphere, and that he made use of conceptions from that general environment to give expression to his own experience and thought. But this dependence is usually conceived of in very general terms, such as Paul's dependence on Hellenism, on Apocalypticism, on Rabbinic Judaism, on Diaspora Judaism, on Essenism, etc. Our study demonstrates the possibility that these larger contexts may have provided but a general background, and that Paul was specifically dependent on individual works, such as the Wisdom of Solomon, for central formulations within his theology.
Keywords: Religion; Religion